Shamans in Asia - Chilson, Clark, 1967-; Knecht, Peter, 1937- (RoutledgeCurzon, 2003)
Shamans are a central feature of many local religions throughout Asia. This title introduces the activities, worldviews, and lives of shamans in Siberia, China, Korea, Japan, Bangladesh and Pakistan.